2018
DOI: 10.1016/j.pmedr.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trends in cervical cancer screening rates using healthcare claims data: United States, 2003–2014

Abstract: Improved understanding of the natural history of cervical cancer has led to changes in screening recommendations, including the addition of the human papillomavirus (HPV) testing as an option in routine screening. Most studies of screening trends have used national self-reported survey data. To better understand recent trends in cervical cancer screening, including cytology (Papanicolaou, or Pap, tests) and human papillomavirus co-tests (HPV + Pap test), we used healthcare claims data to examine screening prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 17 publications
8
65
0
Order By: Relevance
“…Self-reported data from national surveys may overestimate the screening use compared to data based on health-care claims. [53][54][55] Metasummaries of studies comparing self-reported mammogram vs documented screening history showed sensitivity to be between 93% and 95% and specificity to be approximately 62%; the validity and reliability of self-reported responses also varied across sociodemographic subgroups. 56,57 In addition, question wording may impact the accuracy of self-reported mammography.…”
Section: Limitationsmentioning
confidence: 99%
“…Self-reported data from national surveys may overestimate the screening use compared to data based on health-care claims. [53][54][55] Metasummaries of studies comparing self-reported mammogram vs documented screening history showed sensitivity to be between 93% and 95% and specificity to be approximately 62%; the validity and reliability of self-reported responses also varied across sociodemographic subgroups. 56,57 In addition, question wording may impact the accuracy of self-reported mammography.…”
Section: Limitationsmentioning
confidence: 99%
“…The proportion of minority residents per ZCTA was calculated as the difference of 1 minus the proportion of non-Hispanic White (NHW) residents. Age-adjusted cervical cancer incidence and mortality rates by New Jersey county were obtained from the National Cancer Institute (NCI) State Cancer Profiles [ 14 ], which summarizes data from the latest SEER submission (December 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Little population-based data exist on the utilization of and barriers/facilitators to HPV DNA testing in the US, particularly for minority and medically underserved women with a higher risk of developing cervical cancer. The limited population-based studies on HPV co-test utilization have generally demonstrated low utilization across various population subgroups (approximately ≤20% testing rates) [ 9 12 ]; however, more recent data suggest increased HPV co-test utilization by mid-2013 through 2014 in some populations (≥44% to as high as 78%) [ 13 , 14 ]. Recent analysis of the National Breast and Cervical Cancer Early Detection Program (NBCCEDP) have suggested a variety of provider-level factors (e.g., provider characteristics, practices, beliefs, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations